A possible role of oxidative stress in the vanadium-induced cytotoxicity in the MC3T3E1 osteoblast and UMR106 osteosarcoma cell lines - Cortizo, Ana María (2016)
The cytotoxicity and free radical production induced by vanadium compounds were investigated in an osteoblast (MC3T3E1) and an osteosarcoma (UMR106) cell lines in culture. Vanadate induced cell toxicity, reactive oxygen species (ROS) formation and thiobarbituric acid reactive substances (TBARS) increased in a concentration-dependent manner (0.1–10 mM) after 4 h. The concentration–response curve of vanadate-induced cytotoxicity and oxidative stress in MC3T3E1 cells was shifted to the left of the UMR106 curve, suggesting a greater sensitivity of the non-transformed cells in comparison to the osteosarcoma UMR106 cells. Supplementing with vitamin E acetate (80 mM) significantly inhibited ROS and TBARS formation but did not improve the vanadate-dependent decrease in cell number. Other vanadium compounds (vanadyl, pervanadate, and VO:Aspi, a complex of vanadyl(IV) with aspirin) showed different degrees of cell toxicity and induced oxidative stress. Altogether these results suggest that oxidative stress is involved in vanadium induced osteoblastic cytotoxicity, although the mechanism is unknown. © 2000 Elsevier Science Ireland Ltd. All rights reserved.